The adipokine C1q TNF related protein 3 (CTRP3) is elevated in the breast milk of obese mothers - Megan R. Kwon; Eileen Cress; W. Andrew Clark; Arsham Alamian; Yongke Lu; Jonathan M. Peterson (PeerJ, 2018)
Background C1q TNF related protein 3 (CTRP3) is a relatively novel hormonal factor primarily derived from adipose tissue and has anti-diabetic properties. To determine if CTRP3 could play a role in early childhood development, the purpose of this study was to establish the presence of CTRP3 in breast milk (BM) and to determine whether CTRP3 levels were correlated with pregravid obesity status of the mother. Methods Breast milk was collected from breast-feeding mothers who had a pregravid body mass index (BMI) classification of normal weight (BMI 18–25 kg/m2, n = 23) or obese (BMI > 30 kg/m2, n = 14). Immunoprecipitation followed by immunoblot analysis confirmed the presence of CTRP3 in BM. The concentration of CTRP3 in BM samples was determined by ELISA. Additional bioactive components were also measured by commercially available assays: ghrelin, insulin, leptin, adiponectin, interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and glucose. Bioactive components in normal weight and obese mothers were compared using unpaired t-test (parametric) and Mann–Whitney U-test (non-parametric), as appropriate. Results The primary findings of this study are that the adipokine CTRP3 is present in BM and CTRP3 levels are increased with pregravid obesity. Additionally, this study independently confirmed previous work that BM from obese mothers has a higher concentration of insulin and leptin. Further, no differences were observed in BM between obese and normal weight mothers in ghrelin, adiponectin, IL-6, TNF-α, or glucose levels. Conclusion This study identified a novel factor in BM, CTRP3, and showed that BM CTRP3 levels higher in obese mothers. Because of the purported insulin sensitizing effect of CTRP3, it is possible that the elevated levels of CTRP3 in the BM of obese mothers may offset negative effects of elevated leptin and insulin levels in the BM of obese mothers. Future studies will need to be conducted to determine the relevance of CTRP3 in BM and to examine the presence of other adipose tissue-derived hormonal factors.